Ionic‐Liquid Gating of InAs Nanowire‐Based Field‐Effect Transistors. (27th November 2018) - Lieb, Johanna; Demontis, Valeria; Prete, Domenic; Ercolani, Daniele; Zannier, Valentina; Sorba, Lucia; Ono, Shimpei; Beltram, Fabio; Sacépé, Benjamin; Rossella, Francesco
Abstract: Here, the operation of a field‐effect transistor based on a single InAs nanowire gated by an ionic liquid is reported. Liquid gating yields very efficient carrier modulation with a transconductance value 30 times larger than standard back gating with the SiO2 /Si++ substrate. Thanks to this wide modulation, the controlled evolution from semiconductor to metallic‐like behavior in the nanowire is shown. This work provides the first systematic study of ionic‐liquid gating in electronic devices based on individual III–V semiconductor nanowires: this architecture opens the way to a wide range of fundamental and applied studies from the phase transitions to bioelectronics. Abstract : Ionic liquids perform outstandingly as electrolyte gates in field‐effect transistors based on InAs nanowires . The liquid gating exceeds by a factor 30 the efficiency of conventional solid‐state back‐gate. The effective control of the charge carrier density permits to tune the temperature dependence of the electrical resistance from semiconducting to quasi‐metallic. This suggests novel fundamental and applied studies from low‐dimensional phase transitions to ionic‐to‐electronic signal transduction.